Purinergic Signaling as a Regulator of th17 Cell Plasticity - Acuna-Castillo, C (Public Library of Science, 2016)
T helper type 17 (Th17) lymphocytes, characterized by the production of interleukin-17 and other pro-inflammatory cytokines, are present in intestinal lamina propria and have been described as important players driving intestinal inflammation. Recent evidence, supporting the notion of a functional and phenotypic instability of Th17 cells, has shown that Th17 differentiate into type 1 regulatory (Tr1) T cells during the resolution of intestinal inflammation. Moreover, it has been suggested that the expression of CD39 ectonucleotidase endows Th17 cells with immunosuppressive properties. However, the exact role of CD39 ectonucleotidase in Th17 cells has not been studied in the context of intestinal inflammation. Here we show that Th17 cells expressing CD39 ectonucleotidase can hydrolyze ATP and survive to ATP-induced cell death. Moreover, in vitro-generated Th17 cells expressing the CD39 ectonucleotidase produce IL-10 and are less pathogenic than CD39 negative Th17 cells in a model of experimental colitis in Rag-/- mice. Remarkably, we show that CD39 activity regulates the conversion of Th17 cells to IL-10-producing cells in vitro, which is abrogated in the presence of ATP and the CD39-specific inhibitor ARL67156. All these data suggest that CD39 expression by Th17 cells allows the depletion of ATP and is crucial for IL-10 production and survival during the resolution of intestinal inflammation. Copyright: © 2016 Fernández et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.